Islamic proselytizing in digital religion in Indonesia: the challenges of broadcasting regulation - M. Kholili; Ahmad Izudin; Muhammad Lutfi Hakim (Cogent Social Sciences)
This article aims to understand the challenges of broadcasting regulation in Indonesia, particularly in the context of Islamic proselytizing in the digital era. Drawing on 13 in-depth interviews involving observation and documentation with presented four stakeholders such as the government, the independent institutions, online media businesses, and audiences, in Yogyakarta, Indonesia used a case study approach to gain an understanding of this phenomenon. The researchers discovered two different findings. The first is the transformation of audience behaviours in digital religion, which is reflected into three aspects: interactivities, hypermedia or hypertext, and virtual communities. This finding concerns the changing nature of religious ceremonies from traditional to mediatisation, as many content creators or preachers are adapting religious rituals to cater to new digital communities. The second result is that the government has faced challenges in controlling Islamic content, which has led to an increase in Islamic revivalist groups, many of these groups lack the competence to be preachers with proficiency in Islamic knowledge. In addition to this, past regulations have been imposed by the government, but they are unclear in addressing issues related to new media, such as digital platforms for spreading Islamic content with harmonious massages. In fact, the Indonesian government should redefine about the terms of broadcasting pattern for new regulation in order to encompass new media.